Unequal Development in a Global Age: Lessons from Pasuruan - Agus Prianto (Global Review of Tourism and Social Sciences, 2025)
This study critically examines the political economy of regional development in Pasuruan Regency, Indonesia, focusing on twoflagship policies: toll road infrastructure and the agropolitan area program. Using a qualitative case study approach, it reveals how development initiatives—though framed as inclusive are shaped by alliances between state actors, private capital, and regional elites. The analysis shows that while the state maintains a central role, it increasingly functions as a facilitator of market-oriented development, often sidelining local communities and traditional livelihoods. Evidence from interviews, planning documents, andfield observations highlights how technocratic planning, spatial selectivity, and neoliberal rationalities contribute to uneven development outcomes. The study contributes to critical debates on decentralized governance and neoliberalism in Indonesia by exposing how inclusive policy discourses are often undermined by institutional practices that prioritize growth over equity. It calls for more participatory and redistributive approaches to ensure development benefits are equitably shared.